Loss and serendipity, twists and turns in the archives of Enrique Buenaventura's En la diestra de Dios Padre - Andrés Betancourt Morales (Revista Brasileira de Estudos da Presença, 2024)
Loss and serendipity, twists and turns in the archives of Enrique Buenaventura’s En la diestra de Dios Padre1 – This article reviews the various moments of an investigation into the play En la diestra de Dios Padre by Enrique Buenaventura, which was thought to have failed, and its re-direction around the valorization of its sound archives. The exploration of these archives, together with the exploration of photographic documentary pieces, made it possible to establish the scenic text of the second version of the play and the fundamental elements of an act considered as lost, as well as to reconstitute the epilogue of the play in its totality.